2010
DOI: 10.1016/j.aller.2009.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and factors linked to atopic eczema in 10- and 11-year-old schoolchildren. Isaac 2 in Almeria, Spain

Abstract: The prevalence of atopic eczema is similar to that found in other studies within ISAAC Phase I. The most important risk factors for atopic eczema are family and personal history of other atopic diseases and the presence of fungi in the home.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 33 publications
3
4
0
Order By: Relevance
“…In this study, the prevalence of atopic dermatitis over the past 12 months was 14.4%. This rate is similar to those reported in other ISAAC questionnaire-based studies in the Republic of Korea and other developing countries [10,11]. In previous ISAAC questionnaire-based studies, the reported prevalence tended to be higher than in dermatologic examination-based studies [12].…”
Section: Discussionsupporting
confidence: 89%
“…In this study, the prevalence of atopic dermatitis over the past 12 months was 14.4%. This rate is similar to those reported in other ISAAC questionnaire-based studies in the Republic of Korea and other developing countries [10,11]. In previous ISAAC questionnaire-based studies, the reported prevalence tended to be higher than in dermatologic examination-based studies [12].…”
Section: Discussionsupporting
confidence: 89%
“…The prevalence of AD in Seoul, Korea is thus similar to that reported in Western countries in studies that have applied the ISAAC questionnaire [15,16]. The 12-month prevalence of itchy flexural eczema in Seoul was significantly higher in 2008 than in 1995 and 2000, demonstrating that the prevalence of AD continues to increase [10,11].…”
Section: Discussionsupporting
confidence: 71%
“…Atopic dermatitis was common among patients with AR (40%), indeed, to an extent that is higher than that reported in a previous study performed in Spain . Atopic dermatitis has been described as a risk factor for development of AR and even more severe form of AR . In this study, the diagnosis of atopic dermatitis was associated with more severe AR when using m‐ARIA classification.…”
Section: Discussionmentioning
confidence: 68%